Web-based care: a new paradigm in hypertension management?. Issue 6 (November 2008) - Green, Beverly
Beverly B Green, MD, MPH, is a practicing family doctor and preventive care specialist at Group Health Cooperative, a large Seattle-based health plan. She is also an affiliate investigator at the Group Health Center for Health Studies, conducting health services research with a focus on cardiovascular disease and cancer screening. She is the primary investigator for a NIH-funded grant awarded to the Group Health Center for Health Studies, testing whether home blood pressure monitoring, secure messaging and pharmacist care improves hypertension control. Dr Green has over 20 years of experience in the development and implementation of evidence-based guidelines, including guidelines on nutrition, exercise, obesity, hypertension, colon, breast and prostate cancer screening, and osteoporosis. She has authored several papers and book chapters on physical activity, obesity and healthy lifestyle change. She received the Glenn Hartquist Award in 1999, awarded to the Group Health physician who has contributed the most to clinical quality improvement, and was a finalist for the Group Health Lifetime Achievement Award in 2004.